Analisis Putusan Praperadilan dalam Kasus Korupsi di Nagari Sikabau: Tinjauan Hukum Acara Pidana dan Prinsip Keadilan dalam Islam - Sakutra Laya; Riki Zulfiko (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
In the criminal justice system, criminal procedure law in Indonesia is based on the presumption of innocence, which means that the human rights of every individual must be safeguarded and protected. Even so in the view of Islam, law and justice cannot be separated, Allah is the holder of sovereignty, ruler, and at the same time the lawmaker through His revelation in the form of Al-Qur'an and Hadith Rasul. In Decision Number 1/Pid.Pra/2024/PN Plj related to suspects Abdul Razak and Yulasmen, who are suspectedof being inloved in criminal acts of corruption in the form the profit distribution of the pusako ninik mamak palm coorperative in 2018-2021, the researcher is interested in conducting a study of the judge's consideration in granting the parties' pretrial motions and assessing whether these considerations are in accordance with the applicable criminal procedural law provisions. This research uses normative methods with a legislative approach and analysis of court decisions. In accordance with Article 77 of KUHAP, pretrial has the authority to examine the validity of an arrest and detention, as well as to assess whether or not the termination of an investigation or prosecution is valid, including a request for compensation and rehabilitation for a person whose criminal case is terminated at the investigation or prosecution stage.